Cephamometric evaluation of anterior open bite treatment with niti wires and anterior elastics in young adolescents - Atout, Baha Nizar (My University, 2002)
Bu çalışmadaki amacımız yetişkinlerde ön açık kapanışın kapatılmasından sonra tedavinin sefalometrik olarak değerlendirilmesidir. Bu çalışmada ortalama yaşları 13.5 olan 10 hasta yer almaktadır (8 kız,2 erkek). Hastalar Marmara Üniversitesi Dişhekimliği Fakültesinin kliniğinden seçilmişlerdir. Bütün hastalar 1 mm den fazla ön açık kapanışa sahip olup Sınıf I veya hafif Sınıf II kapanış göstermektedirler. Bu çalışmada Kim tekniğinin bir modifikasyonu olarak üst çenede arttırılmış, alt çenede ters Spee eğrisi içeren Ni Ti arklar ve anterior elastikler kullanılmıştır. Tedaviden önce ve ön açık kapanışın düzeltilmesinden hemen sonra lateral sefalometrik filmler çekilmiştir. Sefalometrik analizde bir çok dental parametrenin belirgin değişiklikler gösterdiği belirlenmiştir. Bu değişiklikler aşağıdaki gibidir: Alt kesicilerde ortalama 3 mm ekstrüzyon, 4.56° dikleşme, üst kesicilerde 2.00 mm ekstrüzyon 4.89° dikleşme görülmüştür. Üst ve alt birinci molarlar belirgin biçimde dikleşmiştir (sırasıyla 12.44°, 10.33° ). Aynı zamanda her biri istatistiksel olarak anlamlı olmamakla birlikte 0.33 mm uzamıştır. N-Me ve ANS-Me daki çok az artış dışında (sırasıyla 1.56mm, 1.78mm) bir iskelesel değişiklik görülmemiştir. Overbite alt ve üst kesicilerin uzaması nedeniyle 3.89 mm artmış, overjet ise alt ve üst kesicilerin dikleşmesi nedeniyle 0.89 mm azalmıştır. Sonuç olarak bu teknik genç yetişkinlerin tedavisinde etkilidir. İleriki çalışmalarda sonuçlarımızın stabilitesini uzun dönemde araştırılması önerilmektedir. English

Our aim in this study is cephalometric evaluation of the treatment after the closure of anterior open bite in adolescents. The study involved 10 patients (8 females and 2 males); average age was 13.5 year. They were selected from the clinical intake of the dental faculty of Marmara University. All patients exhibited Class I or mild Class II relationship, with anterior open bite more than 1 mm. In this study we used upper accentuated and lower reverse curved Ni-Ti arch wires and anterior elastics which is a modification for Kim's technique. This modality of treatment was stopped when sufficient incisal overlap was achieved. Lateral cephalometric films were obtained before and immediately after the closure of the open bite. The cephalometric analysis showed that most dental parameters showed significant changes. The significant changes achieved were as follows: the lower incisors extruded with an average of 3.00 mm, and uprighted by 4.56°. The upper incisors extruded 2.00 mm and uprighted by 4.89 °. Both upper and lower first molars uprighted significantly (12.44°,10.33° respectively) while extruded insignificantly, 0.33mm for each. There were no significant skeletal changes except for a slight increase in N-Me and ANS-Me (1.56mm, 1.78mm respectively). The overbite was increased by 3.89 mm, due to the extrusion of the upper and lower incisors, while the overjet was reduced by 0.89 mm which is due to uprighting of both upper and lower incisors. As a conclusion this technique was effective in the treatment of open bite in young adolescents. Further studies are suggested to investigate the long term stability of our results.
Keywords: Ortodonti